Brassinosteroids affect wood development and properties of Fraxinus mandshurica - Lu, Han; Chen, Mingjun; Fu, Meng; Yan, Jialin; Su, Wenlong; Zhan, Yaguang; Zeng, Fansuo (Frontiers in Plant Science, 2023)
Introduction Xylem development plays a crucial role in wood formation in woody plants. In recent years, there has been growing attention towards the impact of brassinosteroids (BRs) on this xylem development. In the present study, we evaluated the dynamic variation of xylem development in Fraxinus mandshurica (female parent, M8) and a novel interspecific hybrid F. mandshurica × Fraxinus sogdiana (1601) from May to August 2020. Methods We obtained RNA-Seq transcriptomes of three tissue types (xylem, phloem, and leaf) to identify the differences in xylem-differentially expressed genes (X-DEGs) and xylem-specifically expressed genes (X-SEGs) in M8 and 1601 variants. We then further evaluated these genes via weighted gene co-expression network analysis (WGCNA) alongside overexpressing FmCPD, a BR biosynthesis enzyme gene, in transient transgenic F. mandshurica. Results Our results indicated that the xylem development cycle of 1601 was extended by 2 weeks compared to that of M8. In addition, during the later wood development stages (secondary wall thickening) of 1601, an increased cellulose content (14%) and a reduced lignin content (11%) was observed. Furthermore, vessel length and width increased by 67% and 37%, respectively, in 1601 compared with those of M8. A total of 4589 X-DEGs were identified, including enzymes related to phenylpropane metabolism, galactose metabolism, BR synthesis, and signal transduction pathways. WGCNA identified hub X-SEGs involved in cellulose synthesis and BR signaling in the 1601 wood formation–related module (CESA8, COR1, C3H14, and C3H15); in contrast, genes involved in phenylpropane metabolism were significantly enriched in the M8 wood formation–related module (CCoAOMT and CCR). Moreover, overexpression of FmCPD in transient transgenic F. mandshurica affected the expression of genes associated with lignin and cellulose biosynthesis signal transduction. Finally, BR content was determined to be approximately 20% lower in the M8 xylem than in the 1601 xylem, and the exogenous application of BRs (24-epi brassinolide) significantly increased the number of xylem cell layers and altered the composition of the secondary cell walls in F. mandshurica. Discussion Our findings suggest that BR biosynthesis and signaling play a critical role in the differing wood development and properties observed between M8 and 1601 F. mandshurica.